Factors Related to Dementia among Elderly Persons in Thailand: A Systematic Review - Sukchan, Phnom; Niyomdecha, Kasfar; Srichaisuwan, Deen (Princess of Naradhiwas University Journal, 2022)
Dementia is a common health problem in the elderly, with 3.4% of which is caused by brain cell degradation that result in loss of ability, affecting daily life. Personal factors such as age, occupation, behavior and so on were found to be associated with dementia. The objective of this study was to summarize the knowledge of studies on factors that correlates dementia among the elderly in Thailand, using a systematic review method. The research studies were from Google scholar and Thai Journals Online (ThaiJO). Then synthesize the reliability of the empirical data according to the Stettler criteria and select 10 synthesized documents to study. The results found that the four main factors related to dementia in the elderly consisted of 1) basic personal factors which were age, sex, marital status, body mass index, morbidity and family members having a history of dementia, 2) economic factors such as education level, reading ability, occupation and income, 3) behavioral factors and health risks such as smoking, exercise, and taking dietary supplements and 4) other factors such as sleep problems. In conclusion, for further of assessment of dementia among the elderly in Thailand, it is suggested to consider the above factors in assessing causes of dementia.